Dissecting the genetic architecture of human personality. - Munafò, MR; Flint, J (2011)
The first candidate gene studies of human personality promised much but, in the fifteen years since their publication, have delivered little in the way of clear evidence for the contribution of specific genetic variants to observed variation in personality traits. This is most likely due to the very small effects conferred by individual loci. The advent of genome-wide association studies has brought growing awareness that high levels of statistical stringency, very large sample sizes, and independent replication will be minimum requirements for future genetic studies of personality. At the same time, evidence from other fields indicates that the genetic architecture of personality is likely to consist of the combined effect of many hundreds, if not thousands, of small effect loci.